Beliefs About Sexual Activity During Pregnancy: A Systematic Review of the Literature - Ribeiro, Meireluci Costa; Scanavino, Marco de Tubino [UNESP]; Sant'Ana do Amaral, Maria Luiza [UNESP]; Moraes Horta, Ana Lucia de; Torloni, Maria Regina (Routledge Journals, Taylor & Francis Ltd, 2017)
The aim of this review is to present the beliefs related to sexual activity during pregnancy. We identified 13 studies (3,122 participants). The main positive beliefs about sex in pregnancy were that it makes labor easier, promotes marital harmony, prevents infidelity, and improves fetal well-being. Negative beliefs were more frequent: that sex could harm the unborn child (cause injuries, miscarriage, or fetal infection) and endanger the pregnancy or maternal health (cause membrane rupture, bleeding, preterm labor, and maternal infection). These findings are useful to clinicians and educational program developers.